Fatal respiratory infection due to ST308 VIM-1-producing Pseudomonas aeruginosa in a lung transplant recipient: case report and review of the literature - M. Carugati (BMC Infectious Diseases, 2020)
Abstract Background Data regarding the prevalence of metallo-β-lactamases (MBLs) among Pseudomonas aeruginosa isolates in cystic fibrosis patients are scarce. Furthermore, there is limited knowledge on the effect of MBL production on patient outcomes. Here we describe a fatal respiratory infection due to P. aeruginosa producing VIM-type MBLs in a lung transplant recipient and the results of the subsequent epidemiological investigation. Case presentation P. aeruginosa isolates collected in the index patient and among patients temporally or spatially linked with the index patient were analyzed in terms of antibiotic susceptibility profile and MBL production. Whole-genome sequencing and phylogenetic reconstruction were also performed for all P. aeruginosa isolates producing VIM-type MBLs. A VIM-producing P. aeruginosa strain was identified in a lung biopsy of a lung transplant recipient with cystic fibrosis. The strain was VIM-1-producer and belonged to the ST308. Despite aggressive treatment, the transplant patient succumbed to the pulmonary infection due to the ST308 strain. A VIM-producing P. aeruginosa strain was also collected from the respiratory samples of a different cystic fibrosis patient attending the same cystic fibrosis center. This isolate harbored the blaVIM-2 gene and belonged to the clone ST175. This patient did not experience an adverse outcome. Conclusions This is the first description of a fatal infection due to P. aeruginosa producing VIM-type MBLs in a lung transplant recipient. The circulation of P. aeruginosa isolates harboring MBLs pose a substantial risk to the cystic fibrosis population due to the limited therapeutic options available and their spreading potential.